2018
DOI: 10.1038/s41598-018-31727-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of cyclophosphamide, leflunomide, corticosteroids, or conservative management alone in patients with IgA nephropathy: a retrospective observational study

Abstract: To compare the long-term efficacy of corticosteroids (P) alone or in combination with cyclophosphamide (CTX), leflunomide (LEF), or Angiotensin-convertase inhibitors or angiotensin II receptor blockers (ACEI/ARB) in treatment for IgA nephropathy (IgAN), 311 patients with IgAN were identified. Therapeutic effectiveness (including progression, partial remission, complete remission) and combined renal endpoint (defined as 30% reduction in eGFR or ESRD) were compared based on different therapies. After immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
2
5
0
2
Order By: Relevance
“…Chen et al found that LEF combined with CS significantly reduced urinary protein, improved albumin and eGFR in patients with IgAN compared with supportive care. [ 56 ] The similar results has been obtained from a meta-analysis. [ 57 ] We found that the long-term efficacy of CTX+CS was better, but its safety concerns may restrict the possible benefits, which was in accordance with the study conducted by Woo et al with a minimum 10 years follow-up.…”
Section: Discussionsupporting
confidence: 78%
“…Chen et al found that LEF combined with CS significantly reduced urinary protein, improved albumin and eGFR in patients with IgAN compared with supportive care. [ 56 ] The similar results has been obtained from a meta-analysis. [ 57 ] We found that the long-term efficacy of CTX+CS was better, but its safety concerns may restrict the possible benefits, which was in accordance with the study conducted by Woo et al with a minimum 10 years follow-up.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study by Noval Rivas et al has strengthened the evidence for potential role of secretory IgA deposition in coronaries of KD patients [ 16 ]. We hypothesize that in progressive KD, these active immune cells/complexes are not fully suppressed by steroids or selective anti-cytokine therapies, and hence require direct cytotoxic alkylating mechanism of cyclophosphamide, which has been effectively used in treatment of other IgA mediated vasculidities [ 17 , 18 ]. We compared clinical management and outcomes in our series to those of 7 previously reported cases in 3 published series [ 9 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…По данным целого ряда исследований известно, что в некоторых случаях естественная эволюция клинических и морфологических проявлений IgAN может быть значительно изменена под влиянием лечения [16][17][18][19][20][21]. Вместе с тем подходы к лечению, определенные в известных международных и местных рекомендациях и основанные на применении блокады ренин-ангиотензиновой системы (РАС) и иммуносупрессивной терапии (ИСТ), имеют невысокую клиническую эффективность по результатам проспективных исследований, в которых частота ремиссий на ИСТ составляла 25-62% (включая полные ремиссии -7,8-55,3%) [22][23][24][25][26][27][28][29]. Как установлено нами ранее, IgAN в отечественной популяции отличается более выраженными клиническими и гистологическими проявлениями, а также неблагоприятным прогнозом, доминируя по распространенности среди других клинико-морфологических фенотипов гломерулярного повреждения [29].…”
Section: ââåäåíèåunclassified
“…Согласно полученным данным ТЭ не увеличивала вероятность развития ремиссии ни в качестве дополнения терапии БРАС, ни в комбинации с КС. Следует отметить, что частота ремиссий в сравниваемых группах достаточно высока, в том числе в сравнении с другими исследованиями [23,25,27,28]. Кроме того, цитируемые метаанализы основывались главным образом на данных ретроспективных исследований, поэтому их результаты вряд ли можно отнести к надежным.…”
Section: îáñóAeäåíèåunclassified